Child Malnutrition and Poverty: The Case of Pakistan (The Pakistan Development Review, 2014)
The role of economic factors, particularly income and consumption, in the wellbeing of a population is well documented. The well-being, however, does not depend solely on these factors, social indicators such as life expectancy, health, education and nutrition serve an important complementary function [Linnemayr, et al. (2008)]. The most significant social problems in many developing countries including Pakistan are widespread child malnutrition, high infant mortality and low literacy. Child malnutrition is considered as the key risk factor for illness and death, contributing to more than half the deaths of children globally [Cheah, et al. (2010)]. It also affects the child morbidity rate and poses threat to their physical and mental development, which results in lower level of educational attainment [Chirwa and Ngalawa (2008)]. The recent literature therefore considers the nutrition status as an important dimension of individual wellbeing [Babatunde, Olagunju, and Fakayode (2011)].